Health Promotion Model "Extracurricular" Approach of Reproductive Health among Early Adolescents - Lidia Hastuti; Wuriani Wuriani; Lilis Lestari; Lestari Makmuriana; Hidayah Hidayah (International Journal of Public Health Science (IJPHS), 2018)
The behavior to maintenance of reproductive organs, and self-adjustment on changes during puberty become its own problems on early adolescence (10-14 years old). True knowledge can improve reproductive health and prevent of free sex behavior end up with unsafe abortion even death in adolescence. School has a major role in shaping positive attitudes in children towards reproductive health at puberty. It is important to find and develop a program of reproductive health school-based in the form of "extracurricular" health reproductive in early adolescence (10-14 years old) not existed in Indonesia up to now. To find and design a model school-based health promotion programs in the form of "extracurricular" reproductive health that can be applied to the early adolescence in school. Qualitative research with a phenomenology approach, to explore models of reproductive health promotion programs in the early adolescence. The mining data was qualitative of focus group discussion (FGD) and in-depth interview. Participants in this research were 36 people of purposive sampling technique into account maximum variation sampling, and data analyze used the thematic analysis. The study results found a reproductive health promotion model school-base with extracurricular approach of reproductive health. The program is carried out outside school hours learning activities on reproductive health, with a study of the self-development, social, physical, sexual violence and the prevention of sexually transmitted infections. Program applied by using approach method and innovative media balance to age of adolescent’s development and involve health workers, teachers and parents.